Development of a laboratory technique for the evaluation of protease enzymes activity in goat and sheep milk. (15th April 2017) - Palomba, Raffaele; Formisano, Giorgio; Arrichiello, Assunta; Auriemma, Giuseppe; Sarubbi, Fiorella
Highlights: Proteolytic activity in sheep and goat milk. Raw milk may have proteolytic activity from endogenous or indigenous origin. A solution containing protease N extracted from Bacillus subtilis was used. The results were independent from the protease content, but depends of substrate. Abstract: The shelf life of milk and its products is strongly influenced by the quality of raw milk. Several bacteria present in raw milk can produce proteases: among them, those from psychotropic microorganisms (e.g. Bacillus subtilis ), which produce enzymes under refrigeration, cause the most serious problem. The interaction of these enzymes with the milk proteins and the main proteolytic enzymes becomes important in determining the quality of the milk. An artificial substrate (azocasein) was used to quantify the enzyme activity through the release of a chromogenic product that was measured spectrophotometrically after clarifying the sample by the addition of trichloroacetic acid. The detection limit and quantification limit were 1.43 and 4.77 mg/ml respectively for sheep milk and, 2.25 and 7.5 mg/ml respectively for goat milk. This method is useful for determining the proteolytic activity in different media and its effectiveness depends on chemical-nutritional characteristics of the sample.